(3GdQSGdI GdbjGSjIs - (3GdJhbGOj, GdHgdhGf, ehSi Hf YHO Gddg, J (B1133 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GYde Cf GdbjGS EeG Cf jJPcQ cdG ebOeJjg Ch jWhi CMO ebOeJjg aEf cGf GdChd aGdCeQ XGgQ hEf cGf GdKGfj adG jNdh EeG Cf Jchf GdebOeI GdePchQI eTJedI dGMO WQaj GdeWdhH Ch dG aEf cGf GdKGfj aXGgQ Cfg GSJKfGFj dh CfJL GdeWdhH s
(3BNQgG (B:s
(3hcd (B( (3L H (B) (3jchf HYV eSGh (B( (3dL (B) (3dcf de fYKQ hbhY GdKGdK aj GdcdGe hEf YKQfG hbhY GdQGHY aj GdcGe bdjdG hGdTQhW hGdVQhH GdhGbYI aj GdeJYGQa LGQjI aj ZjQ GdeJYGQa JCed gPG GdebGe aEfg ef eRGdb GdGbOGes
(3JJdhg fbd aj GdfMhs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3/934s
(3gOjI GdYGQajf (B2 / 482s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdadSaI hGdefWbs